Heat stress levels in judokas during a special performance test conducted at two different ambient temperatures - Palka, T.; Rydzik, L.; Witkowski, K.; Tota, L..; Lech, G.; Ambrozy, T.; Leiva-Arcas, A.; Kubacki, R.; Piotrowska, A.; Wasacz, W.; Czarny, W. (Archives of Budo, 2023)
Background and Study Aim: The exercise metabolism of a judoka during a tournament bout or a single training unit is based primarily on anaerobic processes. Under such conditions of physical stress, significant damage to muscle cells occurs, greater than in typically aerobic efforts. Among the strongest stimuli causing these changes are the mechanical and metabolic stresses associated with the physiological cost of exercise, which can be exacerbated when working at elevated ambient temperatures. The aim of our research was to obtain knowledge about the relationship between the effect of a special fitness test conducted at two different ambient temperatures and the level of heat stress in judokas.